Cyberlibertarianism : the right-wing politics of digital technology - Golumbia, David (Minneapolis : University of Minnesota Press, 2024)
"In a timely challenge to the potent political role of digital technology, Cyberlibertarianism argues that right-wing ideology was built into both the technical and social construction of the digital world from the start. Leveraging more than a decade of research, David Golumbia traces how digital evangelism has driven the worldwide shift toward the political right, concealing inequality, xenophobia, dishonesty, and massive corporate concentrations of wealth and power"--
The Critique of Cyberlibertarianism -- The Dogma of Cyberlibertarianism -- The Forms and Functions of Cyberlibertarianism -- Deregulation and Multistakeholderism : A Case Study of Section 230 -- Digital Technology and the Printing Press -- The Myth of "Free Culture" -- Political Myths -- Cyberlibertarianism and the Far Right -- Computers without Cyberlibertarianism.
Keywords: Libertarianism -- United States; Information technology -- Political aspects -- United States; Social media -- Political aspects -- United States; Data privacy -- United States; Right-wing extremists -- United States -- Attitudes